(3QSGdI oeNJUQI aj Yde Gdhab GdTQjas - (3eMeO Hf LdGd Hf XGgQ Hf LdGd GdOjf GdNLfOj GdeOfjs ((3oeUWai Hf jhfS s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ GdNLfOj GdeOfj Efj LeYJ HJhajb Gddg JYGdi aj gPG GdoeNJUQ GdTQja fHPI ef Yde Jhajb GdCSeGA s
(3BNQgG (B:s
(3MUd dg GdbHhd ef cd CMO hGdQRb GdhGSY hGdSYGOI GdYXei hgPg UhQJg ceG JQi hGddg CYde Je GdcJGH HYhf Gddg Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B- (3HZOGO (B(453) s
Keywords: (3GdMQha h GdChaGbs